Identifying and revealing the geographical variation in Nemopilema nomurai venom metalloprotease and phospholipase A2 activities. (March 2021) - Yu, Chunlin; Yue, Yang; Yin, Xiujing; Li, Rongfeng; Yu, Huahua; Li, Pengcheng
Abstract: Venom geographical variation is common among venomous animals. This phenomenon presents problems in the development of clinical treatments and medicines against envenomation. The venomous giant jellyfish Nemopilema nomurai, Scyphozoan, is a blooming jellyfish species in the Yellow Sea and the East China Sea that causes numerous jellyfish sting cases every year. Metalloprotease and phospholipase A2 (PLA2 ) are the main components in Nemopilema nomurai venom and may activate many toxicities, such as hemolysis, inflammation and lethality. Geographical variation in the content and activity of these enzymes may cause different symptoms and therapeutic problems. For the first time, we verified metalloprotease and PLA2 geographical variation in Nemopilema nomurai venom by performing a comparative analysis of 31 venom samples by SDS-PAGE, analyzing protease zymography, enzymatic activity, and drawing contour maps. Band locations and intensities of SDS-PAGE and protease zymograms showed geographical differences. The enzymatic activities of both metalloprotease and PLA2 showed a trend of geographic regularity. The distribution patterns of these activities are directly shown in contour maps. Metalloproteinase activity was lower near the coast. PLA2 -like activity was lower in the Southern Yellow Sea. We surmised that metalloproteinase and PLA2 -like activities might be related to venom ontogeny and species abundance respectively, and influenced by similar environmental factors. This study provides a theoretical basis for further ecological and medical studies of Nemopilema nomurai jellyfish venom. Graphical abstract: Image 1 Highlights: Nemopilema nomurai nematocyst venom (NnNV) geographical variation were verified. NnNV metalloproteinase (MP) activity was lower near the coast. NnNV PLA2 activity was lower in Southern Yellow Sea. MP and PLA2 activities might be related to ontogeny and abundance respectively.